Molecular determinants of resurgent sodium currents mediated by Navβ4 peptide and A-type FHFs - Xiao, Yucheng; Pan, Yanling; Xiao, Jingyu; Cummins, Theodore R. (Frontiers in Molecular Neuroscience, 2024)
IntroductionResurgent current (INaR) generated by voltage-gated sodium channels (VGSCs) plays an essential role in maintaining high-frequency firing of many neurons and contributes to disease pathophysiology such as epilepsy and painful disorders. Targeting INaR may present a highly promising strategy in the treatment of these diseases. Navβ4 and A-type fibroblast growth factor homologous factors (FHFs) have been identified as two classes of important INaR mediators; however, their receptor sites in VGSCs remain unknown, which hinders the development of novel agents to effectively target INaR.MethodsNavβ4 and FHF4A can mediate INaR generation through the amino acid segment located in their C-terminus and N-terminus, respectively. We mainly employed site-directed mutagenesis, chimera construction and whole-cell patch-clamp recording to explore the receptor sites of Navβ4 peptide and FHF4A in Nav1.7 and Nav1.8.ResultsWe show that the receptor of Navβ4-peptide involves four residues, N395, N945, F1737 and Y1744, in Nav1.7 DI-S6, DII-S6, and DIV-S6. We show that A-type FHFs generating INaR depends on the segment located at the very beginning, not at the distal end, of the FHF4 N-terminus domain. We show that the receptor site of A-type FHFs also resides in VGSC inner pore region. We further show that an asparagine at DIIS6, N891 in Nav1.8, is a major determinant of INaR generated by A-type FHFs in VGSCs.DiscussionCryo-EM structures reveal that the side chains of the critical residues project into the VGSC channel pore. Our findings provide additional evidence that Navβ4 peptide and A-type FHFs function as open-channel pore blockers and highlight channel inner pore region as a hotspot for development of novel agents targeting INaR.